STRATEGI OPTIMALISASI LAYANAN PERPUSTAKAAN SEKOLAH MELALUI PROGRAM “KANJI KUPER” SD NEGERI NGRANCAH - Aris Suharyadi; Beny Dwi Saputra (Nusantara Journal of Information and Library Studies (N-JILS), 2020)
This research aims to find out how the implementation, impact, and constraints of the implementation of the program "Kanji Kuper" (Gerakan Wajib Kunjung Perpustakaan) as a strategy for optimizing library services in elementary schools. This research uses a qualitative approach with descriptive methods. This type of research is a case study because the research setting is in one of the elementary schools that implements the "Kanji Kuper" program. Data collection techniques through direct observation, documentation, and in-depth interviews. Data sources are obtained from informants: principals, library managers, and students. The validity of the data uses the triangulation of sources and techniques. Data is analyzed through data collection, data reduction, data feed and verification or withdrawal of conclusions. The results showed that the implementation of "Kanji Kuper" began by requiring teachers and students to do learning activities in the library. The visit schedule is arranged based on coordination between the class and the library administrator at least once a week. While in the library teachers are obliged to socialize "Kanji Kuper" and motivation by providing assignments to students to utilize the library resources available. There are always products or results made by students during visits to the library. Each month students' work is selected to be displayed in the school as a form of reward. The result of the implementation of the "Kanji Kuper" program is that the number of library visitors has increased dramatically so that it is slowly expected to improve the reading culture of students. The problem is that most students take advantage of the "Kanji Kuper" program just to play in the library so that the resulting task product seems less optimal. Some teachers still think that "Kanji Kuper" only takes up learning time.Keyword: library; school library; library servicesABSTRAKPenelitian ini bertujuan untuk mengetahui bagaimana implementasi, dampak, dan kendala dari pelaksanaan program "Kanji Kuper" (Gerakan Wajib Kunjung Perpustakaan) sebagai strategi optimalisasi layanan perpustakaan di Sekolah Dasar (SD). Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Jenis penelitian ini adalah studi kasus karena setting penelitian berada di salah satu sekolah dasar yang menerapkan program "Kanji Kuper". Teknik pengumpulan data melalui observasi langsung, dokumentasi, dan wawancara mendalam. Sumber data diperoleh dari informan yaitu: kepala sekolah, pengelola perpustakaan, dan siswa. Validitas data menggunakan teknik triangulasi sumber dan teknik data dianalisis melalui langkah-langkah pengumpulan data, reduksi data, sajian data dan verifikasi atau penarikan kesimpulan. Hasil penelitian menunjukkan bahwa implementasi "Kanji Kuper" diawali dengan mewajibkan guru dan siswa melakukan kegiatan pembelajaran di perpustakaan. Jadwal kunjungan disusun berdasarkan koordinasi antara wali kelas dengan pengurus perpustakaan minimal 1 minggu sekali. Selama di perpustakaan guru wajib memberikan sosialisasi "Kanji Kuper" dan motivasi dengan cara memberikan penugasan terhadap siswa agar dapat memanfaatkan sumber daya perpustakaan yang tersedia. Selalu ada produk atau hasil yang dibuat oleh siswa selama berkunjung di perpustakaan. Setiap bulan hasil karya siswa diseleksi untuk dipajang di mading sekolah sebagai bentuk reward. Hasil dari penerapan program "Kanji Kuper" adalah jumlah pengunjung perpustakaan naik drastis sehingga secara perlahan diharapkan dapat meningkatkan budaya membaca siswa. Kendalanya adalah sebagian besar siswa memanfaatkan program "Kanji Kuper" hanya untuk bermain di perpustakaan sehingga produk tugas yang dihasilkan terkesan kurang optimal. Beberapa guru masih beranggapan bahwa "Kanji Kuper" hanya menyita waktu pembelajaran.